Oriented conductive shielding adhesive film, ICT communication equipment and preparation method of oriented conductive shielding adhesive film

By adding sheet-shaped conductive powder, spherical conductive powder and magnetic powder to the conductive filler, and forming a continuous conductive network through magnetic field orientation processing, the problem of degradation of interface adhesion when the existing conductive glue is improved, and efficient electromagnetic shielding and good bonding performance are achieved.

CN119592298APending Publication Date: 2025-03-11SHENZHEN HFC SHIELDING PRODS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411740084.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

While the existing conductive glue improves the electromagnetic shielding effect, it leads to reduced interface adhesion, increased production costs and increased processing difficulty.

Method used

The oriented conductive shielding film is used to add sheet-shaped conductive powder, spherical conductive powder and magnetic powder to the conductive filler, and the magnetic field orientation treatment is used to form a continuous conductive network, optimize the conductive path and reduce the amount of powder filling.

Benefits of technology

It achieves the improvement of electromagnetic shielding effect while maintaining good bonding performance, reduces powder filling, improves mechanical strength and toughness, and reduces signal attenuation and noise interference.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005162431450000141
    Figure BDA0005162431450000141
Patent Text Reader

Abstract

The invention relates to an oriented conductive shielding adhesive film, ICT communication equipment and a preparation method thereof, and belongs to the technical field of electromagnetic shielding materials. The oriented conductive shielding adhesive film is prepared from the following raw materials in parts by weight: 400 to 947 parts of conductive filler, 200 to 310 parts of liquid resin, 1 to 10 parts of solvent, 0.05 to 0.3 part of inhibitor, 5 to 15 parts of curing agent, 1 to 8 parts of catalyst and 1 to 8 parts of thixotropic agent, wherein the conductive filler comprises flaky conductive powder and spherical conductive powder. In the conductive shielding adhesive film, magnetic powder is adsorbed on sheet-shaped conductive powder for magnetization treatment; and the flaky conductive powder is arranged in an oriented manner. Under the condition that the amount of powder is reduced, the adhesive film has good adhesion and can keep a good electromagnetic shielding effect at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of electromagnetic shielding materials, and in particular to an oriented conductive shielding film, ICT communication equipment and a preparation method thereof. Background Art

[0002] With the rapid development of electronic information technology and electrical equipment, modern society is facing an increasingly complex electromagnetic environment. As a byproduct of this environment, electromagnetic interference (EMI) has potential hazards that cannot be underestimated. It not only affects the stable operation of electrical equipment, but may also lead to information security leaks and pose a serious threat to the overall performance of electronic systems. Therefore, the research and development and application of electromagnetic shielding technology has become a key focus of the global scientific and industrial communities.

[0003] In the research of electromagnetic shielding materials, pressure-sensitive conductive adhesive has gradually become the research focus in this field due to its convenient operation and good processing adaptability. Traditional conductive adhesives usually use doped functional fillers (such as metal powders, carbon-based materials, etc.) to improve their conductivity and electromagnetic shielding properties. Although high filling content can enhance the electromagnetic shielding effect, the problems that come with it cannot be ignored, including reduced interface adhesion, increased production costs, and increased processing difficulty. Summary of the invention

[0004] In view of the deficiencies in the prior art, the purpose of the embodiments of the present application includes providing an oriented conductive shielding film, ICT communication equipment and a preparation method thereof, which can take into account interface adhesion while also enhancing the electromagnetic shielding effect.

[0005] In the first aspect, the embodiments of the present application provide an oriented conductive shielding adhesive film, wherein the glue raw materials, in parts by weight, include: 400-947 parts of conductive filler, 200-310 parts of liquid resin, 1-10 parts of solvent, 0.05-0.3 parts of inhibitor, 5-15 parts of curing agent, 1-8 parts of catalyst and 1-8 parts of thixotropic agent; wherein the conductive filler includes flaky conductive powder, spherical conductive powder and magnetic powder, and in the conductive shielding adhesive film, magnetic powder is adsorbed on some flaky conductive powder for magnetization treatment, and the flaky conductive powder is oriented.

[0006] The conductive filler of the present application includes flaky conductive powder, spherical conductive powder and magnetic powder, wherein the magnetic powder is adsorbed on the flaky conductive powder, and the flaky conductive powder is oriented, that is, the diameter direction of the flaky conductive powder is parallel to the direction of the magnetic field. Such an oriented arrangement can form a continuous conductive network. Through this arrangement, the conductive path can be optimized, thereby effectively enhancing the electromagnetic shielding capability; and, unlike the adhesion degradation problem caused by the high filling amount of the traditional conductive glue, the adhesive film of the present application can still maintain good bonding performance by moderately reducing the powder filling amount (can be reduced to 60%). The combination of flaky powder, spherical powder and magnetic powder of the present application provides a variety of conductive mechanisms. The surface contact of the flaky powder and the point contact of the spherical powder are combined to form a three-dimensional conductive network, which enhances the overall conductivity, so that the adhesive film performs well in circuit connection and signal transmission, and reduces signal attenuation and noise interference. In addition, under the synergistic effect of the liquid resin and the thixotropic agent, the adhesive film has good adhesion and thixotropy, so the adhesive film will not collapse or tilt after being taken out of the magnetic field. The addition of curing agent and catalyst can promote the curing reaction of the film, so that the film can reach the final hardness and performance in a shorter time. At the same time, the addition of inhibitor can prevent over-fast curing and maintain the flexibility of construction time.

[0007] In some embodiments of the present application, the mass ratio of the flaky conductive powder to the magnetic powder is (3-10):1.

[0008] By limiting the mass ratio of flaky conductive powder to magnetic powder to (3-10):1, maintaining a high ratio of flaky conductive powder helps to improve the mechanical strength and toughness of the film and enhance its bonding performance with the substrate after curing; at the same time, moderate addition of magnetic powder can make the film have good conductivity while enhancing the electromagnetic shielding effect; within this ratio range, the conductivity and shielding ability can be better balanced, so that the film performs well in resisting electromagnetic interference.

[0009] In some embodiments of the present application, the flaky conductive powder includes one or more of graphene powder with a flake diameter of 5-30μm, nickel-plated silver-coated aluminum powder with a flake diameter of 5-30μm, silver powder with a flake diameter of 5-30μm, copper powder with a flake diameter of 5-30μm and nickel-carbon with a flake diameter of 5-30μm; and / or, the spherical conductive powder includes one or more of spherical silver-coated aluminum powder, spherical silver powder, spherical copper powder and spherical silver-plated copper powder; and / or, the magnetic powder includes one or more of nano-ferroferric oxide, manganese zinc ferrite and nickel zinc ferrite.

[0010] In some embodiments of the present application, the conductive filler includes: 30-60 parts of graphene powder with a flake size of 15-25 μm, 150-200 parts of nickel-plated silver-coated aluminum powder with a flake size of 35-50 μm, 80-150 parts of spherical silver-coated aluminum powder with a particle size of 0.6-2 μm and 300-450 parts of spherical silver-coated aluminum powder with a particle size of 50-80 μm.

[0011] By designing the composition ratio and particle size of the conductive filler within the above range, the film can have excellent conductive properties and electromagnetic shielding effects, while also improving the mechanical properties and thixotropy of the film.

[0012] In some embodiments of the present application, the liquid resin includes 100-130 parts of vinyl silicone oil, 50-80 parts of MVQ resin and 50-100 parts of methyl vinyl rubber.

[0013] The combination of vinyl silicone oil, MVQ resin and methyl vinyl rubber gives the film excellent fluidity, mechanical strength, heat resistance and adhesion. Among them, vinyl silicone oil has excellent fluidity; MVQ resin has excellent heat resistance and mechanical strength, which can improve the stability of the film in high temperature environment; the addition of methyl vinyl rubber improves the elasticity of the film, so that the finished product can adapt to the thermal expansion and contraction of the substrate, and enhances the adhesion between different materials; at the same time, the combination of vinyl silicone oil and MVQ resin can achieve a faster curing speed and maintain good physical properties after curing, shortening the production cycle and improving production efficiency.

[0014] In some embodiments of the present application, the viscosity of the vinyl silicone oil is 500-10000 mPa.s.

[0015] The viscosity of vinyl silicone oil ranges from 500-10000mPa·s and has excellent fluidity, which enables the glue to be evenly distributed during the coating process, reducing bubbles and unevenness, thereby forming a smooth coating.

[0016] In some embodiments of the present application, the inhibitor includes hexynyl cyclohexanol.

[0017] In some embodiments of the present application, the curing agent includes terminal H-containing silicone oil.

[0018] In some embodiments of the present application, the catalyst includes a platinum water catalyst.

[0019] In some embodiments of the present application, the solvent includes hydrocarbon solvent oil.

[0020] In some embodiments of the present application, the thixotropic agent includes one or more of fumed silica, organic bentonite, hydrogenated castor oil, polyamide wax and nano-black carbon black.

[0021] In a second aspect, an embodiment of the present application provides an ICT communication device, comprising any of the above-mentioned oriented conductive shielding films.

[0022] The above-mentioned oriented conductive shielding film is used in ICT communication equipment. The film has excellent electromagnetic shielding effect through optimized conductive filler combination and oriented design, which can effectively resist external electromagnetic interference, thereby improving the signal stability and data transmission quality of the equipment. Moreover, the good thixotropy and bonding properties of the film make it easy to operate during the coating and bonding process of complex structures, and can form a uniform and durable conductive layer. In addition, its excellent heat resistance and mechanical strength ensure the reliability and durability of the equipment in various working environments.

[0023] In the third aspect, an embodiment of the present application provides a method for preparing the above-mentioned ICT communication equipment, including: stirring and mixing flaky conductive powder and magnetic powder to obtain magnetized powder; stirring and mixing the magnetized powder, liquid resin, thixotropic agent, inhibitor, curing agent, and solvent, and then adding a catalyst to obtain prefabricated glue; dispensing the prefabricated glue at the target position of the ICT device body, and placing the glued ICT device body into a magnetic field for magnetic field orientation treatment, so that the sheet diameter direction of the flaky conductive powder is parallel to the direction of the magnetic field; and then heating and curing the device to cure the glue at the target position of the ICT device body to form an ICT communication device.

[0024] In this preparation method, the preparation of the film and the application of the film to the ICT communication equipment are integrated operations, that is, the application is to apply glue to the location where the equipment is applied, then orient it in a magnetic field, and finally heat and cure it to obtain an ICT communication device with the oriented conductive shielding film. In this preparation method, by using anisotropic powder and implementing an orientation process, the diameter direction of the flaky conductive powder is parallel to the direction of the magnetic field. This arrangement method can make the conductive particles form a more continuous conductive network in the film, enhance the contact and overlap between the particles, effectively reduce the transmittance of electromagnetic waves, and thus improve the shielding effect of electromagnetic interference; it can also reduce the filling of powder.

[0025] In some embodiments of the present application, the magnetic field strength of the magnetic field is 5-8 T; or / and, the prefabricated glue is subjected to a degassing treatment before dispensing.

[0026] By controlling the magnetic field strength within the range of 5-8 T, particle orientation can be promoted, electromagnetic shielding and conductivity can be enhanced, and the glue curing process can be optimized. In addition, degassing the prefabricated glue before dispensing can remove bubbles in the glue and reduce the defects that may be formed by bubbles after curing, thereby improving the bonding strength and overall performance of the glue.

[0027] In some embodiments of the present application, the stirring speed is 1000-3500 r / min, and the stirring time is 30-90 min.

[0028] By controlling the stirring speed to 1000-3500r / min and the stirring time to 30-90min, the raw materials can be mixed evenly, the particles can be well dispersed, the conductivity and shielding properties can be improved, the foam generation can be controlled, and the production efficiency can be improved. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0030] The following is a detailed description of an oriented conductive shielding glue, ICT communication equipment and a preparation method thereof according to an embodiment of the present application.

[0031] An embodiment of the present application provides an oriented conductive shielding adhesive film, in which the glue raw materials include, by weight: 400-947 parts of conductive filler, 200-310 parts of liquid resin, 1-10 parts of solvent, 0.05-0.3 parts of inhibitor, 5-15 parts of curing agent, 1-8 parts of catalyst and 1-8 parts of thixotropic agent; wherein the conductive filler includes flaky conductive powder, spherical conductive powder and magnetic powder, and in the conductive shielding adhesive film, magnetic powder is adsorbed on some flaky conductive powders for magnetization treatment, and the flaky conductive powders are oriented.

[0032] The conductive filler of the present application includes flaky conductive powder, spherical conductive powder and magnetic powder, wherein some flaky conductive powders are adsorbed with magnetic powder for magnetization treatment, and the flaky conductive powders are oriented, that is, the diameter direction of the flaky conductive powders is parallel to the direction of the magnetic field. Such an oriented arrangement can make the spherical conductive powders and the flaky conductive powders overlap better on the one hand, and can form a continuous conductive network, and on the other hand, it can also reduce the filling of the powder. The amount of the conductive filler powder of the present application can be reduced to 60%; therefore, through this arrangement, the amount of powder filling can be reduced, and the conductive path can be optimized, so that the film can form a more effective shielding effect when facing electromagnetic interference, reduce the penetration of external electromagnetic waves, and improve the electromagnetic compatibility of electronic equipment; and it can also reduce the filling of the powder. The amount of the conductive filler powder of the present application can be reduced to 60%. At the same time, the combination of flaky powder, spherical powder and magnetic powder provides a variety of conductive mechanisms. The surface contact of the flaky powder and the point contact of the spherical powder are combined to form a three-dimensional conductive network, which enhances the overall conductivity, so that the glue performs well in circuit connection and signal transmission, and reduces signal attenuation and noise interference. In addition, the synergistic effect of the liquid resin and the thixotropic agent makes the adhesive film have good fluidity during application and maintain appropriate viscosity in a static state. The thixotropic agent reduces the viscosity when shear force is applied, which is convenient for coating and dispensing, and then restores the viscosity when static, so that the glue does not flow. Therefore, the glue will not collapse or tilt after being taken out of the magnetic field; this makes the glue easy to operate during the coating process, and can form a uniform and durable bonding layer to adapt to surfaces of various complex shapes. The addition of curing agents and catalysts can promote the curing reaction of the glue, so that the glue can reach the final hardness and performance in a shorter time. At the same time, the addition of inhibitors can prevent too fast curing and maintain the flexibility of construction time.

[0033] In the present application, the mass ratio of the flaky conductive powder to the magnetic powder is (3-10): 1. As an example, the mass ratio of the flaky conductive powder to the magnetic powder includes but is not limited to 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1.

[0034] The mass ratio of the flaky conductive powder to the magnetic powder is limited to the range of (3-10):1, wherein the amount of the flaky conductive powder is dominant, thereby forming a more continuous and effective conductive network. Moreover, maintaining a high ratio of the flaky conductive powder helps to improve the mechanical strength and toughness of the film and enhance its bonding performance with the substrate after curing. By controlling the magnetic powder within the above ratio range, the conductive path can be enhanced, so that the film has good conductivity and can also enhance the electromagnetic shielding effect.

[0035] The flaky conductive powder includes one or more of graphene powder with a flake diameter of 5-30 μm, nickel-plated silver-coated aluminum powder with a flake diameter of 5-30 μm, silver powder with a flake diameter of 5-30 μm, copper powder with a flake diameter of 5-30 μm and nickel-carbon with a flake diameter of 5-30 μm; and / or, the spherical conductive powder includes one or more of spherical silver-coated aluminum powder, spherical silver powder, spherical copper powder and spherical silver-plated copper powder; and / or, the magnetic powder includes one or more of nano-ferroferric oxide, manganese-zinc ferrite and nickel-zinc ferrite.

[0036] Among them, the above-mentioned flaky conductive powder has extremely high conductivity and can effectively improve the conductivity of the glue. Its flaky structure helps to form a stable conductive network, allowing the current to be smoothly conducted. Magnetized powder, such as nano-ferroferric oxide, can effectively absorb and shield electromagnetic waves, especially in the high-frequency range. Its nano-scale particle size increases the surface area and improves the shielding effect, making the glue perform better in the electromagnetic interference environment. In addition, the flaky conductive powder provides structural support, while the spherical conductive powder helps to improve toughness and reduce brittleness. Therefore, this combination can make the adhesive film have good mechanical strength and durability after curing. At the same time, limiting the sheet diameter to the range of 5-30μm can improve the fluidity and sizing performance of the glue, which is more conducive to the uniform dispersion of the material. When shear force is applied, the glue can flow smoothly, and when it is stationary, it maintains appropriate viscosity, which enhances the convenience of construction.

[0037] As an example, the conductive filler includes: 30-60 parts of graphene powder with a flake size of 15-25 μm, 150-200 parts of nickel-plated silver-coated aluminum powder with a flake size of 35-50 μm, 80-150 parts of spherical silver-coated aluminum powder with a particle size of 0.6-2 μm and 300-450 parts of spherical silver-coated aluminum powder with a particle size of 50-80 μm.

[0038] Among them, graphene powder with a flake size of 15-25μm can effectively form a conductive network and significantly improve the conductivity of current, while 150-200 parts of nickel-plated silver-coated aluminum powder with a flake size of 35-50μm and 300-450 parts of nickel-plated silver-coated aluminum powder with a particle size of 50-80μm further enhance the overall conductivity. In addition, 80-150 parts of spherical silver-coated aluminum powder with a particle size of 0.6-2μm absorb high-frequency electromagnetic waves and combine with silver-coated aluminum powder with a larger particle size to provide multi-level electromagnetic shielding capabilities. This combination also improves the mechanical strength and toughness of the film, improves the durability of the film after curing, and enables the film to adapt to various harsh application environments. At the same time, by designing the particle size of various powders within the above range, the film can have good fluidity when shear force is applied, and maintain appropriate viscosity when stationary, which is convenient for construction and uniform coating.

[0039] In the present application, the liquid resin includes 100-130 parts of vinyl silicone oil, 50-80 parts of MVQ resin and 50-100 parts of methyl vinyl rubber. The viscosity of the vinyl silicone oil is 500-10000mPa.s. The vinyl silicone oil with a viscosity of 500-10000mPa·s has good fluidity and lubricity, which can make the glue evenly distributed during the coating process to form a smooth coating; the addition of MVQ resin enhances the mechanical strength and heat resistance of the glue and improves its stability in high temperature or harsh environment. In addition, the presence of methyl vinyl rubber further enhances the elasticity and adhesion of the film, making it easier to form a firm bond with the substrate.

[0040] In the present application, the inhibitor includes alkynyl cyclohexanol, the curing agent includes terminal H-containing silicone oil, the catalyst includes platinum water catalyst, the solvent includes hydrocarbon solvent oil, and the thixotropic agent includes one or more of fumed silica, organic bentonite, hydrogenated castor oil, polyamide wax and nano black carbon black. The types of solvent hydrocarbon solvent oil include but are not limited to D30, D40, D50, D60, D80, D100, D110 and D130.

[0041] An embodiment of the present application provides an ICT communication device, which uses the above-mentioned oriented conductive shielding glue.

[0042] The preparation of the ICT communication equipment is introduced below.

[0043] A method for preparing the above-mentioned ICT communication device comprises the following steps:

[0044] (1) Prepare glue raw materials

[0045] The oriented conductive shielding adhesive film comprises, by weight, 400-947 parts of conductive filler, 200-310 parts of liquid resin, 1-10 parts of solvent, 0.05-0.3 parts of inhibitor, 5-15 parts of curing agent, 1-8 parts of catalyst and 1-8 parts of thixotropic agent.

[0046] (2) Magnetization treatment of flaky conductive powder

[0047] The flaky conductive powder and the magnetic powder are added to a high-speed vortex mixer and mixed for 5-20 minutes. The magnetic powder is adsorbed on the flaky conductive powder by mechanical force and van der Waals force, and the excess magnetic powder is filtered by sieving to obtain processed magnetic powder with magnetization function.

[0048] (3) Rubber dispersion and mixing

[0049] The liquid resin and the thixotropic agent are premixed uniformly in a centrifugal mixer, and then the magnetized powder and other conductive fillers after magnetization in step (1) are added to the centrifugal mixer for further dispersion and mixing, and finally the inhibitor, curing agent and catalyst are added in sequence, and the solvent is added at the same time to react to obtain a prefabricated glue.

[0050] (4) Glue dispensing

[0051] The prefabricated glue in step (3) is degassed and filled into a specific EFD needle tube by a filling machine, and operated in conjunction with a glue dispensing machine. The size of the extruder nozzle can be used to control the dispensing diameter. At the same time, due to the good thixotropy of the product, it can be dispensed into semicircular, triangular, and rectangular shapes without collapse, and finally a conductive adhesive strip that matches the application gap of the relevant equipment shell is produced.

[0052] (5) Orientation and shaping

[0053] The device housing with the conductive glue applied in step (4) is placed in a magnetic field device with the magnetic field direction in the axial direction. Under the action of the magnetic field, the diameter direction of the flaky conductive powder is parallel to the magnetic field direction, so as to better link the conductive path and make the product have better conductive performance and shielding effect; then the device is placed in a heatable tunnel furnace, and heated and cured to obtain a conductive adhesive film with good resilience, conductivity and bonding with the sealing track of the device housing. The heating temperature is 100-130°C and the heating time is 15-45min.

[0054] This application uses anisotropic powders and implements an orientation process to optimize the arrangement of conductive particles in the vertical and horizontal planes, thereby significantly improving the electromagnetic shielding performance and reducing the filling of powders. This arrangement allows the conductive particles to form a more continuous conductive network in the film, enhances the contact and overlap between particles, effectively reduces the transmittance of electromagnetic waves, and thus improves the shielding effect of electromagnetic interference. This optimized conductive path not only improves the stability of the signal, but also reduces the signal loss of the device in a high-frequency environment. This application is to apply glue to the location where the device is applied, then orient it in a magnetic field, and finally heat and cure it. That is to say, the preparation of the glue in this application and the application of the glue to ICT communication equipment are an integrated operation.

[0055] Wherein, the magnetic field strength of the magnetic field is 5-8T; or / and, the prefabricated glue is degassed before dispensing. As an example, the magnetic field strength of the magnetic field includes but is not limited to 5T, 6T, 7T, and 8T. Within this intensity range, the interaction force between the powders can be overcome, and the rapid orientation of the particles in the magnetic field can be promoted, thereby forming a more ordered conductive structure, optimizing the conductive path, and improving the electromagnetic shielding performance. When the conductive particles are arranged in a more orderly manner, the contact area between adjacent particles increases, forming a more continuous conductive network, which can significantly reduce the transmittance of electromagnetic waves, thereby enhancing the ability of the device to resist electromagnetic interference. At a magnetic field strength of 5-8T, the contact and overlap between the conductive particles are closer, and this close contact promotes the smooth conduction of current, reduces resistance, and enhances overall conductivity. This improvement is particularly important for the transmission of high-frequency signals and can effectively reduce signal attenuation. Moreover, within the range of magnetic field strength, the glue can maintain the initial orientation of the particles during the curing process to prevent the particles from being rearranged due to temperature changes or external forces after curing.

[0056] Degassing can remove bubbles from the glue and reduce the defects that may be formed after curing, thereby improving the bonding strength and overall performance of the glue. It also helps to evenly distribute the conductive particles, thereby improving conductivity and electromagnetic shielding effects.

[0057] In the present application, the stirring speed is 1000-3500 r / min, and the stirring time is 30-90 min.

[0058] At a stirring speed of 1000-3500r / min, different types of powders (such as flaky conductive powder and magnetic powder) can be effectively mixed. The stirring time is set within 30-90min, which can make the powder fully dispersed in the liquid resin. The evenly dispersed conductive particles can form a more continuous conductive network, thereby enhancing the current conduction ability and electromagnetic shielding effect, and improving the performance of the overall material.

[0059] The features and performance of the present application are further described in detail below in conjunction with the embodiments.

[0060] Example 1

[0061] This embodiment provides an ICT communication device, using the oriented conductive shielding film provided by this application, and the preparation thereof includes:

[0062] (1) Prepare glue raw materials

[0063] Liquid resin: vinyl silicone oil 110g, methyl vinyl raw rubber 80g, MVQ resin 60g.

[0064] Conductive filler: 50g graphene powder with a flake diameter of 20μm, 180g nickel-plated silver-coated aluminum powder with a flake diameter of 40μm, spherical powder: 100g spherical silver-coated aluminum powder with a size of 1μm, 420g spherical silver-coated aluminum powder with a size of 70μm, and 5g nano-ferroferric oxide.

[0065] Additives: 0.15g of cyclohexyl alcohol, 12g of H-terminated silicone oil, 5g of platinum water catalyst, 5g of nano-black carbon black, and 5g of hydrocarbon solvent oil D130.

[0066] (2) Magnetization treatment of flaky conductive powder

[0067] Flake graphene powder, flaky nickel-silver-coated aluminum powder and nano-ferroferric oxide are added to a high-speed vortex mixer and mixed for 15 minutes. The magnetic powder is adsorbed on the above-mentioned flaky conductive powder by mechanical force and van der Waals force, and the excess nano-ferroferric oxide powder is sieved to obtain magnetized powder.

[0068] (3) Rubber dispersion and mixing

[0069] The liquid resin and nano-black carbon black are premixed uniformly in a centrifugal mixer, and then the magnetized powder in step (2) and other conductive fillers are added to the centrifugal mixer for further dispersion and mixing, and finally cyclohexyl alcohol, end-containing H silicone oil and platinum water catalyst are added in sequence, and hydrocarbon solvent oil D130 is added at the same time to react to obtain a prefabricated glue.

[0070] (4) Glue dispensing

[0071] The prefabricated glue in step (3) is degassed and filled into a specific EFG needle tube by a filling machine, and the glue is applied to the target position of the equipment in conjunction with the glue dispensing machine.

[0072] (5) Orientation and shaping

[0073] The device with the conductive glue applied in step (4) is placed in a magnetic field device with an axial magnetic field direction, and the magnetic field strength is set to 6T. Under the action of the magnetic field, the diameter direction of the flaky graphene powder is parallel to the magnetic field direction; then the device is placed in a tunnel furnace at 120°C and heated for 30 minutes. The glue is cured on the device by heating.

[0074] Example 2

[0075] This embodiment is basically the same as Embodiment 1, except that 25 g of nano-ferroferric oxide is added, that is, the mass ratio of flaky graphene powder to nano-ferroferric oxide is 2:1.

[0076] Example 3

[0077] This embodiment is basically the same as Embodiment 1, except that 4.2 g of nano-ferroferric oxide is added, that is, the mass ratio of flaky graphene powder to nano-ferroferric oxide is 12:1.

[0078] Example 4

[0079] This embodiment is basically the same as the embodiment 1, except that the total amount of the conductive filler accounts for 65% of all the raw materials.

[0080] (1) Prepare glue raw materials

[0081] Liquid resin: vinyl silicone oil 110g, methyl vinyl raw rubber 80g, MVQ resin 60g.

[0082] Conductive filler: 35g graphene powder with a flake diameter of 20μm, 140g nickel-plated silver-coated aluminum powder with a flake diameter of 40μm, spherical powder: 70g spherical silver-coated aluminum powder with a size of 1μm, 270g spherical silver-coated aluminum powder with a size of 70μm, and 3.5g nano-ferroferric oxide.

[0083] Additives: 0.15g of cyclohexyl alcohol, 12g of H-terminated silicone oil, 5g of platinum water catalyst, 5g of nano-black carbon black, and 5g of hydrocarbon solvent oil D130.

[0084] Comparative Example 1

[0085] This comparative example is basically the same as Example 1, except that flaky graphene powder and flaky silver-coated aluminum powder are used, and no magnetization treatment is performed, that is, step (2) in Example 1 is not performed.

[0086] (1) Prepare glue raw materials

[0087] Liquid resin: vinyl silicone oil 110g, methyl vinyl raw rubber 80g, MVQ resin 60g.

[0088] Conductive filler: 50g of graphene powder with a flake diameter of 20μm, 180g of silver-coated aluminum powder with a flake diameter of 40μm, spherical powder: 100g of spherical silver-coated aluminum powder with a size of 1μm, 380g of spherical silver-coated aluminum powder with a size of 70μm, and 5g of nano-ferroferric oxide.

[0089] Additives: 0.15g of cyclohexyl alcohol, 12g of H-terminated silicone oil, 5g of platinum water catalyst, 5g of nano-black carbon black, and 5g of hydrocarbon solvent oil D130.

[0090] (2) Dispersion and mixing of rubber materials

[0091] The liquid resin and nano-black carbon black are premixed uniformly in a centrifugal mixer, and the conductive filler is added into the centrifugal mixer for further dispersion and mixing, and finally alkynyl cyclohexanol, terminal H-containing silicone oil and platinum water catalyst are added in sequence, and hydrocarbon solvent oil D130 is added at the same time to react to obtain prefabricated glue.

[0092] (3) Glue dispensing

[0093] The prefabricated glue in step (2) is degassed and filled into a specific EFG needle tube by a filling machine, and the glue is applied to the target position of the equipment in conjunction with the glue dispensing machine.

[0094] (4) Orientation and shaping

[0095] The device with the conductive glue applied in step (3) is placed in a magnetic field device with an axial magnetic field direction, and the magnetic field strength is set to 6T. Under the action of the magnetic field, the diameter direction of the flaky graphene powder is parallel to the magnetic field direction; then the device is placed in a tunnel furnace at 120°C and heated for 30 minutes. The glue is cured on the device by heating.

[0096] Comparative Example 2

[0097] This comparative example is basically the same as Example 1, except that 50 g of graphene powder with a flake diameter of 20 μm and 180 g of nickel-plated silver-coated aluminum powder with a flake diameter of 40 μm are replaced with 20 μm spherical silver-coated aluminum powder and 40 μm spherical silver-coated aluminum powder.

[0098] Comparative Example 3

[0099] This comparative example is basically the same as Example 1, except that no thixotropic agent is added.

[0100] Test Example 1

[0101] This test example measures the performance of the films in the above-mentioned Examples 1-4 and Comparative Examples 1-3, including the following items: hardness, tensile strength, bonding strength, volume resistivity, shielding performance, extrusion rate and dispensing shape stability. Among them, the hardness is carried out in accordance with the ASTM D2240 standard, the tensile strength is carried out in accordance with the ASTM D 412 standard, the bonding strength is carried out in accordance with the GB / T7124-2008 standard, the volume resistivity is carried out in accordance with the ASTM D 257 standard, and the shielding effectiveness is carried out in accordance with the GB / T 30142-2013 standard.

[0102] Extrusion rate test method: Use a 30cc EFD needle tube with an inner diameter of 2.56mm for the extrusion nozzle, and test the extrusion weight for 1 minute under an air pressure of 90psi.

[0103] Test method for shape stability of glue dispensing: Use a jig with a hollow size of 20*20mm and a height of 3mm, fill it with glue, then remove the jig, and check whether the glue film has flow and collapse after 30 minutes. If there is no flow and collapse, the shape stability of glue dispensing is good, otherwise it is poor.

[0104] Please see Table 1 for the above performance test results.

[0105] Table 1

[0106]

[0107] It can be seen from Table 1 that the oriented conductive shielding film provided in the present application has good adhesion and electromagnetic shielding effect.

[0108] By comparing Examples 1-3, it can be seen that when the mass ratio of the flaky conductive powder to the magnetic powder is (3-10):1, it is more conducive to improving the electromagnetic shielding effect.

[0109] By comparing Example 1 and Comparative Example 1, it can be seen that the flaky graphene powder and the flaky nickel-silver-coated aluminum powder are not magnetized. Even if magnetic powder is added, the flaky graphene powder and the flaky nickel-silver-coated aluminum powder cannot be oriented after being treated with a magnetic field, resulting in poor shielding performance.

[0110] By comparing Example 1 and Comparative Example 2, it can be seen that the absence of flaky powders will deteriorate the overlap of the powders, thereby causing a decrease in shielding effectiveness.

[0111] By comparing Example 1 and Comparative Example 3, it can be seen that without adding a thixotropic agent, the glue cannot maintain its shape after being extruded and flows, resulting in poor orientation of the flaky powder and poor shielding effectiveness.

[0112] By comparing Examples 1-3, it can be found that in Example 2, the mass ratio of flaky graphene powder to nano-ferroferric oxide is 2:1, and the proportion of nano-ferroferric oxide is large, resulting in more magnetic powder and decreased conductivity; in Example 3, the mass ratio of flaky graphene powder to nano-ferroferric oxide is 12:1, and the proportion of nano-ferroferric oxide is small, that is, less magnetic powder, resulting in poor magnetization of graphene and decreased conductivity. Therefore, controlling the mass ratio of flaky conductive powder to magnetic powder to (3-10):1 is more conducive to improving the conductivity and shielding performance of the film.

[0113] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.

Claims

1. An oriented conductive shielding film, characterized in that: In parts by weight, the glue raw materials include: 400-947 parts of conductive filler, 200-310 parts of liquid resin, 1-10 parts of solvent, 0.05-0.3 parts of inhibitor, 5-15 parts of curing agent, 1-8 parts of catalyst and 1-8 parts of thixotropic agent; The conductive filler includes flaky conductive powder and spherical conductive powder; in the conductive shielding film, part of the flaky conductive powder is subjected to magnetization treatment by adsorbing magnetic powder, and the flaky conductive powder is arranged in an oriented manner.

2. The oriented conductive shielding film according to claim 1, characterized in that: The mass ratio of the flaky conductive powder to the magnetic powder is (3-10):

1.

3. The oriented conductive shielding film according to claim 2, characterized in that: The flaky conductive powder includes one or more of graphene powder with a flake diameter of 5-30 μm, nickel-plated silver-coated aluminum powder with a flake diameter of 5-30 μm, silver powder with a flake diameter of 5-30 μm, copper powder with a flake diameter of 5-30 μm, and nickel-carbon with a flake diameter of 5-30 μm; and / or, the spherical conductive powder includes one or more of spherical silver-coated aluminum powder, spherical silver powder, spherical copper powder, and spherical silver-plated copper powder; and / or, the magnetic powder includes one or more of nano-ferroferric oxide, manganese-zinc ferrite, and nickel-zinc ferrite; Optionally, the conductive filler includes: 30-60 parts of graphene powder with a flake size of 15-25 μm, 150-200 parts of nickel-plated silver-coated aluminum powder with a flake size of 35-50 μm, 80-150 parts of spherical silver-coated aluminum powder with a particle size of 0.6-2 μm and 300-450 parts of spherical silver-coated aluminum powder with a particle size of 50-80 μm.

4. The oriented conductive shielding adhesive film according to any one of claims 1 to 3, characterized in that: The liquid resin comprises 100-130 parts of vinyl silicone oil, 50-80 parts of MVQ resin and 50-100 parts of methyl vinyl rubber.

5. The oriented conductive shielding film according to claim 4, characterized in that: The viscosity of the vinyl silicone oil is 500-10000 mPa.s.

6. The oriented conductive shielding adhesive film according to any one of claims 1 to 3, characterized in that: The inhibitors include hexynyl cyclohexanol; Optionally, the curing agent includes terminal H-containing silicone oil; Optionally, the catalyst comprises a platinum water catalyst; Optionally, the solvent includes hydrocarbon solvent oil; Optionally, the thixotropic agent includes one or more of fumed silica, organic bentonite, hydrogenated castor oil, polyamide wax and nano-black carbon black.

7. An ICT communication device, comprising the oriented conductive shielding adhesive film according to any one of claims 1 to 6.

8. A method for preparing an ICT communication device as claimed in claim 7, characterized in that: include: The flaky conductive powder and the magnetic powder are stirred and mixed to obtain magnetized flaky conductive powder; the magnetized flaky conductive powder, the liquid resin, the thixotropic agent, the inhibitor, the curing agent, and the solvent are stirred and mixed, and then the catalyst is added to obtain prefabricated glue; The prefabricated glue is dispensed at the target position of the ICT device body, and the ICT device body with the dispensed glue is placed in a magnetic field for magnetic field orientation treatment so that the diameter direction of the flaky conductive powder is parallel to the direction of the magnetic field; then the device is heated and cured so that the glue is cured at the target position of the ICT device body to form the ICT communication device.

9. The preparation method according to claim 8, characterized in that: The magnetic field strength of the magnetic field is 5-8T; Or / and, the prefabricated glue is subjected to a degassing treatment before dispensing.

10. The preparation method according to claim 8 or 9, characterized in that: The stirring speed is 1000-3500 r / min, and the stirring time is 30-90 min.